2022
DOI: 10.1063/5.0102219
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-dependent photoluminescence of Eu-activated aluminate hydride Sr3−x AxAlO4H:Eu2+ (A = Ca, Ba; x = 0, 1): Application of advanced U-determination technique for luminescence wavelength prediction

Abstract: The increasing attention on the unique properties of oxyhydride materials motivates the exploration of their potential applications in optical fields, and the theoretical studies of their luminescence properties are still under progress. Here, we report the experimental and theoretical high-pressure photoluminescence (PL) studies on Eu-activated Sr3– x AxAlO4H ( A = Ca and Ba; x = 0 and 1) oxyhydride materials. Under hydrostatic pressures from ambient pressure up to 6.41 GPa, the luminescence band in all the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For the LnNbO 4 series of structures, it was also shown that [LnO 8 ] is significantly more compressible than [NbO 6 ], and that this inhomogeneous compressibility within the lattice can lead directly to irregular changes in bond lengths . Of course, the similar phenomenon that bond lengths of phosphors increase under high pressure has been reported . The Raman vibration peaks at decompression back to 0 GPa were the same as the initial ones, which indicated that the crystal structure has a good stability of pressure recovery and facilitates applications in pressure sensing.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…For the LnNbO 4 series of structures, it was also shown that [LnO 8 ] is significantly more compressible than [NbO 6 ], and that this inhomogeneous compressibility within the lattice can lead directly to irregular changes in bond lengths . Of course, the similar phenomenon that bond lengths of phosphors increase under high pressure has been reported . The Raman vibration peaks at decompression back to 0 GPa were the same as the initial ones, which indicated that the crystal structure has a good stability of pressure recovery and facilitates applications in pressure sensing.…”
Section: Resultsmentioning
confidence: 54%
“…16 Of course, the similar phenomenon that bond lengths of phosphors increase under high pressure has been reported. 17 The Raman vibration peaks at decompression back to 0 GPa were the same as the initial ones, which indicated that the crystal structure has a good stability of pressure recovery and facilitates applications in pressure sensing.…”
Section: Resultsmentioning
confidence: 59%
“…To obtain a highly sensitive pressure sensor, materials that are easily compressible and have large local structural changes under high-pressure conditions are promising. For example, the pressure-sensing properties of Eu 2+ -doped phosphors are 1.4 nm GPa −1 for Ca 3 Y 2 (SiO 4 ) 3 :Eu 2+ , 247 2.2 nm GPa −1 for CaF 2 :Eu 2+ , 238 ∼2.6 nm GPa −1 for Sr 2 BaAlO 4 H, 253 and 19 nm GPa −1 for BaCN 2 :Eu 2+ . 239 The spectral shift is larger in host compounds with high compressibility due to H − ions or molecular anions such as NCN 2− than in compounds with rigid structures.…”
Section: Current and Future Applicationsmentioning
confidence: 99%